Newly Discovered Mechanisms of Antibiotic Self-Resistance with Multiple Enzymes Acting at Different Locations and Stages - Xiaorong Chen; Hai-Xue Pan; Gong-Li Tang (Antibiotics, 2022)
Self-resistance determinants are essential for the biosynthesis of bioactive natural products and are closely related to drug resistance in clinical settings. The study of self-resistance mechanisms has long moved forward on the discovery of new resistance genes and the characterization of enzymatic reactions catalyzed by these proteins. However, as more examples of self-resistance have been reported, it has been revealed that the enzymatic reactions contribute to self-protection are not confined to the cellular location where the final toxic compounds are present. In this review, we summarize representative examples of self-resistance mechanisms for bioactive natural products functional at different cell locations to explore the models of resistance strategies involved. Moreover, we also highlight those resistance determinants that are widespread in nature and describe the applications of self-resistance genes in natural product mining to interrogate the landscape of self-resistance genes in drug resistance-related new drug discovery.